Heterologous AD5-nCOV plus CoronaVac versus homologous CoronaVac vaccination: a randomized phase 4 trial - Li, Jingxin; Hou, Lihua; Guo, Xiling; Jin, Pengfei; Wu, Shipo; Zhu, Jiahong; Pan, Hongxing; Wang, Xue; Song, Zhizhou; Wan, Jingxuan; Cui, Lunbiao; Li, Junqiang; et al. (Nature medicine, 2022)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants and the waning of vaccine-elicited neutralizing antibodies suggests that additional coronavirus disease 2019 (COVID-19) vaccine doses may be needed for individuals who initially received CoronaVac. We evaluated the safety and immunogenicity of the recombinant adenovirus type 5 (AD5)-vectored COVID-19 vaccine Convidecia as a heterologous booster versus those of CoronaVac as homologous booster in adults previously vaccinated with CoronaVac in an ongoing, randomized, observer-blinded, parallel-controlled phase 4 trial ( NCT04892459 ). Adults who had received two doses of CoronaVac in the past 3–6 months were vaccinated with Convidecia ( n = 96) or CoronaVac ( n = 102). Adults who had received one dose of CoronaVac in the past 1–3 months were also vaccinated with Convidecia ( n = 51) or CoronaVac ( n = 50). The co-primary endpoints were the occurrence of adverse reactions within 28 d after vaccination and geometric mean titers (GMTs) of neutralizing antibodies against live wild-type SARS-CoV-2 virus at 14 d after booster vaccination. Adverse reactions after vaccination were significantly more frequent in Convidecia recipients but were generally mild to moderate in all treatment groups. Heterologous boosting with Convidecia elicited significantly increased GMTs of neutralizing antibody against SARS-CoV-2 than homologous boosting with CoronaVac in participants who had previously received one or two doses of CoronaVac. These data suggest that heterologous boosting with Convidecia following initial vaccination with CoronaVac is safe and more immunogenic than homologous boosting. Heterologous vaccination with Convidecia, a recombinant adenovirus type 5-vectored COVID-19 vaccine, after one or two doses of CoronaVac, an inactivated SARS-CoV-2 vaccine, is more reactogenic but elicits significantly higher levels of neutralizing antibodies than homologous vaccination.